2019
DOI: 10.1038/s12276-019-0335-y
|View full text |Cite
|
Sign up to set email alerts
|

Gadd45β promotes regeneration after injury through TGFβ-dependent restitution in experimental colitis

Abstract: Dysregulated immune responses and impaired function in intestinal epithelial cells contribute to the pathogenesis of inflammatory bowel disease (IBD). Growth arrest and DNA damage-inducible 45 beta (Gadd45β) has been implicated in the pathogenesis of various inflammatory symptoms. However, the role of Gadd45β in IBD is completely unknown. This study aimed to evaluate the role of Gadd45β in IBD. Gadd45β-KO mice exhibited drastically greater susceptibility to dextran sulfate sodium (DSS)-induced colitis and mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 43 publications
4
24
1
Order By: Relevance
“…Previously, 14 we found that Gadd45β can regulate TGF signalling pathways in intestinal epithelial cells. To determine whether…”
Section: The Roles Of Gadd45β On Tgf Signalling Pathways In Vitro Amentioning
confidence: 81%
See 1 more Smart Citation
“…Previously, 14 we found that Gadd45β can regulate TGF signalling pathways in intestinal epithelial cells. To determine whether…”
Section: The Roles Of Gadd45β On Tgf Signalling Pathways In Vitro Amentioning
confidence: 81%
“…[21][22][23] Recent studies in experimental animals have shown that Gadd45β is involved in the pathogenesis of various diseases. 14,24,25 In the present study, Gadd45β KO mice were used and UUO surgery was carried out to induce early stage CKD. immune cell infiltration and inflammation, and fibrosis was further investigated in mouse kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA from Kidney cortex region was isolated using TRIzol reagent (Thermo Fisher Scientific) according to manufacturer’s instructions 52 . Double-stranded cDNA synthesis was prepared by using the iScript cDNA Synthesis Kit (BioRad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Kidney tissues (cortex) or cell lysates were homogenized in RIPA (50 mM Tris–HCl, 150 mM NaCl, 1% NP40, 0.5% Na-deoxycholate, and 0.1% SDS) buffer with protease inhibitor cocktail (Roche Applied Science, Penzberg, Germany) 52 . Protein concentration was determined by using the Bradford assay.…”
Section: Methodsmentioning
confidence: 99%
“… 25 26 MDSC-derived ROS are the major inducers of the IEC damage, but MDSC-derived transforming growth factor-β (TGF-β) promotes IEC repair. 27 These double effects drive chronic inflammation. Under the colonic inflammatory milieu, MDSCs downregulate the expression of CCAAT/enhancer-binding protein beta (CEBPβ), a critical transcription factor associated with the suppressive function of MDSCs, and secreted increased levels of proinflammatory molecules.…”
Section: Role Of Mdscs/ilcs/the Gut Microbiota In the Pathogenesis Ofmentioning
confidence: 99%